Whole-Genome Diversification Analysis of the Hornbeam Species Reveals Speciation and Adaptation Among Closely Related Species - Zheng, Zeyu; Li, Ying; Li, Minjie; Li, Guiting; Du, Xin; Hongyin, Hu; Yin, Mou; Lu, Zhiqiang; Zhang, Xu; Shrestha, Nawal; Liu, Jianquan; Yang, Yongzhi (Frontiers in Plant Science, 2021)
Speciation, the basis for the generation of biological diversity, has a central place in evolutionary and ecological research. How species diverged and adapted to different habitats is one of the most exciting areas in speciation studies. Here, we sequenced 55 individuals from three close related Carpinus species, and we found C. tibetana showed a very high inner relatedness, which reflecting the extremely small effective population size. We also found Carpinus monbeigiana and C. mollicoma are the most related species that distributed in the central and north-west forest of Yunnan and south-east of Yunnan and Mount Emei, Sichuan, respectively. The following speciation analysis between C. monbeigiana and C. mollicoma revealed that two species diverged at ~5Mya and accompanying bidirectional gene flow. A total of 291 and 223 highly diverged and copy number variants (CNVs) genes, and 269 positive selected genes between those two species. Genes associated with those diverged and positive selected regions were mainly involved in regulation, developmental and responding to stress, which consisted with adapting to their habitats. This detail case of diversification and adaption study and the important genomic resource will accelerate the speciation studies in the future. In addition, we researched a local hornbeam species in Tibet and found a great population decline small genetic divergence, which indicated it was in danger of extinction.